Interbody fusion in degenerative lumbar spinal stenosis with additional posterolateral fusion using Escherichia coli-derived bone morphogenetic protein-2: A Pilot study. Issue 24 (12th June 2020) - Choi, Sung Hoon; Koo, Ja Wook; Choe, DaeHyun; Hur, Jeong Min; Kim, Dong-Hong; Kang, Chang-Nam
Abstract : Abstract: This case series investigated the efficacy and optimal dose of Escherichia coli -derived bone morphogenetic protein-2 (E.BMP-2) as a bone graft substitute for additional posterolateral spinal fusion, accompanying interbody fusion procedures, for treating lumbar degenerative spinal stenosis. This study focused on the optimal dose for each segment and the efficacy of E.BMP-2 as a substitute for autogenous iliac bone graft. Ten patients were enrolled from January 2015 to December 2015, and underwent an additional posterolateral fusion procedure, with 2.5 mg of E.BMP-2 followed by decompression, transpedicular fixation, and interbody fusion. The mean follow-up period was 13.9 months, and regular radiological examinations were performed in every case. Clinical outcomes were measured with a visual analog scale for back pain (VAS-BP), and leg pain (VAS-LP) and the Korean Oswestry Disability Index (K-ODI). All parameters were assessed preoperatively and postoperatively at 12 months. All 18 segments treated with E.BMP-2 completely fused in 6 months as observed on both simple radiography and computed tomography. The mean fusion period was 4.5 months on simple radiography. At 12 months follow-up, VAS-BP, VAS-LP, and K-ODI scores (1.9 ± 1.5, 1.9 ± 1.9, 11.0 ± 6.6, respectively) had improved significantly compared to preoperative scores (5.5 ± 1.9, 6.5 ± 1.9, and 49.9 ± 11.5, respectively, P  < .05). There were no postoperative wound infections, neurological symptoms, or complications associated with the use of E.BMP-2 during the follow-up period. E.BMP-2 could be used to enhance the outcomes in posterolateral spinal fusion following interbody fusion surgery. In the present study, 2.5 mg of the E.BMP-2 per segment was sufficient to obtain bony union in posterolateral fusion surgery. Further large-scale trials with long-term follow-up are necessary to evaluate the various complications related to the use of E.BMP-2.